Physical properties of cassava starch–carnauba wax emulsion films as affected by component proportions - Ito, Edson Noriyuki (2014)
Properties of glycerol-plasticised cassava starch–carnauba wax emulsion films were studied as functions of carnauba wax/starch (CW/S) ratios. Increases in CW concentrations improved elongation, but impaired tensile strength and elastic modulus, suggesting a plasticising effect by CW and/or the emulsifier. CW reduced water solubility of the films and decreased their water vapour permeability (WVP) up to CW/S ratios of 0.15–0.20, probably because of the decreased water solubility. Higher CW concentrations resulted in increased WVP, possibly due to starch matrix loosening. The opacity imparted by high CW concentrations in films could compromise some applications. The Tg of starch and the expected CW effects on it were not evidenced by DSC thermograms, but CW seems to have affected starch crystallisation, maybe by forming complexes with amylose and/or amylopectin